God in the tumult of the global square : religion in global civil society - Juergensmeyer, Mark; Griego, Dinah, 1957-; Soboslai, John, 1978- (University of California Press, 2015)
"How is religion changing in the twenty-first century? In the global era, religion has leapt into the world stage, though in contradictory ways. Some religious activists are antagonistic and engage in protests, violent acts, and political challenges. Others are positive and help to shape an emerging transnational civil society. A new global religion may be in the making, providing a moral and spiritual basis for a worldwide community of concern about environmental issues, human rights, and international peace. This book explores all of these directions, based on a five-year Luce Foundation project that involved religious leaders, scholars, and public figures in workshops held in Cairo, Moscow, Delhi, Shanghai, Buenos Aires, and Santa Barbara. In this book, the voices of these religious observers around the world are heard expressing both the hopes and fears about new forms of religion in the global age"--Provided by publisher